2016
DOI: 10.1186/s13567-016-0345-x
|View full text |Cite
|
Sign up to set email alerts
|

Serum-derived exosomes from non-viremic animals previously exposed to the porcine respiratory and reproductive virus contain antigenic viral proteins

Abstract: PRRSV is the etiological agent of one of the most important swine diseases with a significant economic burden worldwide and limitations in vaccinology. Exosomes are 30–100 nm vesicles of endocytic origin. Remarkably, immunizations with exosomes containing antigens from tumors or pathogens are capable of eliciting protective immune responses, albeit variably, in cancer and infectious diseases. Here we describe the isolation, molecular composition and immunogenicity of serum-derived exosomes from naïve animals, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 47 publications
(52 reference statements)
2
44
0
Order By: Relevance
“…The role of exosomes in the transfer of infectious agents between cells and tissues has been postulated and demonstrated in several infections. Current studies on exosomes predominately focus on infection and pathogenic mechanisms of human viruses, with little emphasis on the interaction of exosomes and non-human animal virus infection outside of porcine reproductive and respiratory syndrome virus (PRRSV), newcastle disease virus (NDV) and foot-and-month disease viruses (FMDV) [25,28,32]. Exosomes contributed to the virus replication and transmission in the above virus infection, playing various functions as delivering viral components and promoting virus replication at the recipient cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of exosomes in the transfer of infectious agents between cells and tissues has been postulated and demonstrated in several infections. Current studies on exosomes predominately focus on infection and pathogenic mechanisms of human viruses, with little emphasis on the interaction of exosomes and non-human animal virus infection outside of porcine reproductive and respiratory syndrome virus (PRRSV), newcastle disease virus (NDV) and foot-and-month disease viruses (FMDV) [25,28,32]. Exosomes contributed to the virus replication and transmission in the above virus infection, playing various functions as delivering viral components and promoting virus replication at the recipient cells.…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes have proved to carry pathogen-associated materials of infected cells, along with the host components [1,16,25,28]. The viral protein, RNAs even viral particles have been identified in exosomes from virus-infected cells [7,12,28,29]. To characterize the molecular composition of the exosomes, we performed mass spectrometry on the proteins contained in the exosomes for proteomic analysis.…”
Section: Exosomes Delivered Cpiv3 Components and Established Productimentioning
confidence: 99%
“…The main target cells for PRRSV infection are certain lineages of monocytes/macrophages in vivo. The PRRSV effect on JAK-STAT signaling in T cells would be indirect, such as by exosomes from infected cells (Garcia-Nicolas et al, 2016;Montaner-Tarbes et al, 2016). But its interference of the JAK-STAT signaling in infected macrophages would have significant consequence as the response of PAMs against viral or bacterial pathogens is critical in determining the outcome of infection in the host.…”
Section: Prrsv's Effect On Stat2/5/6 Signalingmentioning
confidence: 99%
“…We previously analyzed the secretome of cells infected with PRRSV and found that approximately 72.4% of all the secretory proteins identified were listed in the ExoCarta database (17), suggesting that the release of exosomal proteins was strongly activated by PRRSV infection. A recent study also identified viral proteins of PRRSV in serumderived exosomes from pigs actively or previously infected with PRRSV (18).…”
mentioning
confidence: 94%